REKONSTRUKSI NONPARAMETRIK DYNAMICAL DARK ENERGY MENGGUNAKAN DATA COSMIC CHRONOMETER DAN SUPERNOVA TIPE IA - Jihan Purwanto, Vaneissya
The acceleration of expanding universe which was one of the results of Supernova Ia observations in 1998 has provided a new understanding in cosmology. One solution that could explain it is the existence of a negative pressure component of the universe known as dark energy. The cosmological constant () is one of the simplest models that have constant equations of state parameter, w = ????1. Although is supported by many observations, there are still problems with namely ne-tuning problem and coincidence problem. To solve these problems, a time-dependent dynamical dark energy (DDE) model was introduced. In addition to the theory-motivated DDE model, a phenomenological DDE model based on reconstruction from observational data is also proposed which is expected to provide constraints and directions for the development more formal model. This Final Project aims to reconstruct the parameters of dark energy's equation of state non-parametrically based on the results of observations. In reconstructing the equation of state parameters dark energy, Hubble parameter from the cosmic chronometers observation and the distance modulus from the type Ia supernovae observation, Pantheon, are used. The nonparametric reconstruction in this Final Project used gaussian process which was performed by package GaPP. The results of the two reconstructions from cosmic chronometers data and type Ia supernovae observation, were then compared. It was found that the error of the reconstruction of the dark energy equation of state parameters with the SN Ia Pantheon data was smaller than the error obtained with the cosmic chronometer data. A combined reconstruction of the two data was carried out with a dierent initialization scenario from the reference paper. Nevertheless, the results obtained did not match the reference.